(untitled) (Archaeologia Adriatica, 2022)
The personality cult of the ruler, glorification of monarchical power and placing of prominent individuals on a heroic and divine pedestal were social phenomena present in developed civilisations from ancient times. The Roman imperial cult, a religious and political institution based on identifying and worshipping the emperor as a deity and promoting imperial power, served as an instrument for strengthening Roman rule and romanising the newly conquered territories of the Roman Empire. While the focus of worship was primarily Roman emperors, important in propagating imperial ideology were also their wives, as well as other members of the ruling family. Despite not enjoying the same rights as their spouses, Roman empresses nevertheless actively, as well as indirectly, participated in public and political events and used the privileges of their social status to contribute to the shaping of imperial power and Roman society. Drawing on previous research of the social, political and religious characteristics of the imperial cult, this paper will briefly review the social and political power of the most influential Roman empresses and princesses, with an emphasis on the devotion to their cult in the Province of Dalmatia from the Julio-Claudian dynasty to AD 315.